Xylanase Production by Aspergillus niger Using Agro-Industrial Residues and Tween Surfactants: A Non-Parametric Analysis - Arif Rahman Hakim; Noor Isnaini Azkiya; Wahyuni Ningsih; Mufid Mufid; Arum Kusuma Wardani; Nisa’ Ulana Al Mukharromah (Politeknik Negeri Malang, 2026)
Xylanase plays a key role in hydrolyzing xylan, yet large-scale enzyme production remains limited by the high cost of purified xylan substrates. Although lignocellulosic agricultural residues offer a promising low-cost alternative, their effectiveness as substrates for Aspergillus niger and the influence of process additives on enzyme performance are not fully understood. This study addresses this gap by evaluating sugarcane bagasse and palm kernel cake as economical substrates and examining how substrate type, substrate concentration, and surfactant selection affect xylanase specific activity. Fermentation experiments were conducted using substrate concentrations of 1.5–3.0% (w/v) supplemented with Tween 20, Tween 60, or Tween 80, followed by statistical analysis using the Kruskal–Wallis test and Bonferroni-corrected Mann–Whitney U tests. Substrate concentration (p = 0.016) and surfactant type (p < 0.001) significantly influenced specific activity, whereas substrate type did not (p = 0.224). The highest activity (4.380 ± 0.052 IU/mg; median = 1.9113) was achieved using 3.0% palm kernel cake with Tween 20. These findings demonstrate that optimizing substrate load and surfactant choice is crucial for enhancing xylanase production from low-cost agro-industrial residues, providing practical insights for cost-efficient enzyme bioprocess development.